Perkembangan Financial Technology Terkait Central Bank Digital Currency (CBDC) terhadap Transmisi Kebijakan Moneter dan Makroekonomi - Soleha, Safnah; Hikmah Indri Yani Harahap; Tri Wina Sabrina; Maryam Batubara (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
The purpose of this study is to determine the development of financial technology related to central bank digital currency (CBDC) on the transmission of monetary and macroeconomic policies. The advancement of financial technology (fintech) continues to show a significant increase in today's digital age. This research uses descriptive qualitative research methods with literature studies. The descriptive method used in this research is to describe the direction or process of research development. In brief, it can be concluded that CBDC is electronic money issued by the central bank and can be accessed universally. on the transmission of monetary policy in Indonesia can be shown by the effect of changes in BI 7DRR on banking rates both deposit and credit rates. If the economy is in recession, Bank Indonesia will implement a loose monetary policy by lowering the benchmark interest rate so that economic activity increases. macroeconomics is part of economics that explores economic events and problems holistically as a unit. Macroeconomics also focuses attention on the role of the state in regulating economic activity. The development of fintech, which is in line with the increasingly wide open access to digital finance, has great potential to increase public access to the financial sector.